Obesity in cases undergoing the surgical procedure of lung lobectomy: risk or benefit? - Tulinský,Lubomír (2022)
SUMMARY OBJECTIVE: The aim of the study was to evaluate the effect of body mass index on patients’ short-term results following lung lobectomy. METHODS: In this retrospective study, we compared the perioperative and short-term postoperative results of obese (BMI≥30 kg/m2) versus non-obese patients (BMI<30 kg/m2) who underwent anatomical lung resection for cancer. The two groups had the same distribution of input risk factors and the same ratio of surgical approaches (thoracoscopy vs. thoracotomy). RESULTS: The study included a total of 144 patients: 48 obese and 96 non-obese patients. Both groups had the same ratio of thoracoscopic vs. thoracotomy approach (50/50%), and were comparable in terms of demographics and clinical data. The g roups did not significantly differ in the frequency of perioperative or postoperative complications. Postoperative morbidity was higher among non-obese patients (34.4 vs. 27.1%), but this difference was not statistically significant (p=0.053). Hospital stay was similar in both study groups (p=0.100). Surgery time was significantly longer among obese patients (p=0.133). Postoperative mortality was comparable between the study groups (p=0.167). CONCLUSIONS: Obesity does not increase the frequency of perioperative and postoperative complications in patients after lung lobectomy. The slightly better results in obese patients suggest that obesity may have some protective role.